Sexual Violence in Islamic Boarding Schools As A Social and Educational Problem: Analysis Of Violence Based on Galtung’s Perspective - Ahmad Abrori; Cucu Nurhayati; Ida Rosyidah; Vinita Susanti (Sosio-Didaktika: Social Science Education Journal, 2026)
Sexual violence in Islamic boarding schools is often viewed as an individual behavioural deviation, and responses to this problem tend to focus solely on the perpetrator. This study aims to examine sexual violence in Islamic Boarding Schools as a systemic phenomenon resulting from the interaction among direct, structural, and cultural violence based on the perspective of Johan Galtung’s theory of violence. This research used a qualitative approach, applying a case study design to Islamic Boarding Schools in West Java. Data were collected through in-depth interviews with perpetrators, Islamic Boarding School’s administrators, regional Ministry of Religious Affairs officials, and women’s activists, supported by limited observation and analysis of court-ruling documents. The data was analyzed thematically by linking empirical findings to the frameworks of direct, structural, and cultural violence. This study also analyzed the prevention of sexual violence in Islamic Boarding Schools. The results showed that sexual violence in Islamic Boarding Schools did not only include sexual harassment and exploitation by authority figures (direct violence) but also violence caused by the hierarchical, closed, and minimally supervised structure of Islamic Boarding Schools (structural violence), and violence legitimized by patriarchal cultural values, victim stigma, gender-biased religious interpretations, and a culture of excessive respect for kyai or spiritual leaders (cultural violence). To prevent sexual violence in Islamic Boarding Schools, it is essential to enhance institutional oversight, safeguard students, and foster a cultural shift. This study confirms the applicability of Galtung’s theory in understanding violence within religious-based educational settings and recommends a comprehensive, multidimensional prevention strategy. Keywords: Sexual Violence, Structural Violence, Cultural Violence, Islamic Boarding Schools, Power Relations